Parenting Stress in Turkish Mothers of Infants With Cleft Lip and/or Palate. (June 2020) - Boztepe, Handan; Çınar, Sevil; Özgür, MD, Fatma Figen
Objective: To explore parenting stress and factors affecting the mothers of infants with cleft lip and/or palate (CL/P) in Turkey. Design and Participants: The study compared mothers of infants born with CL/P (n = 90) with mothers of healthy infants (n = 90). Mothers completed the data collection form, the Parenting Stress Index-Short Form, and the Multidimensional Scale of Perceived Social Support. Results: Mothers of infants born with CL/P had higher mean parenting stress scores than the control mothers. A significant negative relationship was found between social support and parenting stress for mothers of infants born with CL/P but was not related for control mothers. Among mothers with an infant with CL/P, the mean parenting stress scores were higher for mothers preoperatively than mothers responding postoperatively. Among mothers with an infant with a cleft, higher stress was found for diagnosis after birth, not breastfeeding, feeding difficulties, lack of fathers' support, perceived difficult infant temperament, blame, anger, and concern for the future. Conclusion: Parenting stress was higher and social support was lower for mothers of infants with a cleft. Treatment teams can design interventions aimed at factors related to stress, such as addressing feeding issues, teaching coping skills, and linking to social support.